Comparative evaluation of the pump mode and turbine mode performance of a large vaned-voluted centrifugal pump - Yang, Shijie; Li, Puxi; Lu, Zhaoheng; Xiao, Ruofu; Zhu, Di; Lin, Kun; Tao, Ran (Frontiers in Energy Research, 2022)
Large vaned-voluted centrifugal pump is a general machine used for large-scale water diversion. As a vane-type hydraulic machinery, it also has the ability of reversible operation. With the introduction of policies to reduce carbon emissions, the proportion of unstable new energy use has increased. The existing large centrifugal pump unit can realize the function of reverse power transfer. For peak shaving and valley filling of power grid, it has high feasibility and economy. In this paper, a large vaned-voluted centrifugal pump is simulated numerically, its external characteristics and flow state under positive and negative rotation are obtained, its performance is predicted by BEP method, and it is found that pump reversal can run at the optimum efficiency point with higher flow rate and head. Error analysis is carried out for different formulas. The FED distribution of flow energy dissipation for different flow rates under positive and negative rotation is analyzed. It is found that the main energy loss locates on suction side of blade, inlet and outlet part of blade and tail part of guide blade head. By comparing the FED distribution under the same flow conditions with positive and reverse rotation, it is found that the high energy loss area of blade mainly exists in inlet and outlet part of blade in pump mode. The high energy loss area of the blades in turbine mode mainly exists in the inlet part of the blades. This study is of great significance to the operation of low-carbon power grid assisted by existing reservoirs and hydraulic machinery.